Dynamic Faces 2010
DOI: 10.7551/mitpress/9780262014533.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Moving Faces: The Interplay of Two Recognition Systems

Abstract: The human face is a captivating stimulus, even when it is stationary. In motion, however, the face comes to life and offers us a myriad of information about the intent and personality of its owner. Through facial movements such as expressions, we can gauge a person's current state of mind. By perceiving the movements of the mouth as a friend speaks, a conversation becomes more intelligible in a noisy environment. Through the rigid movement of the head and the direction of eye gaze, we can follow another person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…It should be mentioned that the two prosopagnosia studies above only included congenitally prosopagnosic patients, rather than acquired prosopagnosic patients. As noted in O'Toole and Roark ( 2010 ), the observed dissociation between static and dynamic facial information processing reflects the possibility that the ability to process facial movements has been developed to compensate for impaired static face processing. One study found that an acquired prosopagnosic patient exhibited deficits in abilities required to recognize faces from both static and dynamic facial information (Lander et al, 2004 ).…”
Section: Facial Motion Improves Face Recognitionmentioning
confidence: 82%
See 4 more Smart Citations
“…It should be mentioned that the two prosopagnosia studies above only included congenitally prosopagnosic patients, rather than acquired prosopagnosic patients. As noted in O'Toole and Roark ( 2010 ), the observed dissociation between static and dynamic facial information processing reflects the possibility that the ability to process facial movements has been developed to compensate for impaired static face processing. One study found that an acquired prosopagnosic patient exhibited deficits in abilities required to recognize faces from both static and dynamic facial information (Lander et al, 2004 ).…”
Section: Facial Motion Improves Face Recognitionmentioning
confidence: 82%
“…Since the publication of this initial finding, other researchers have consistently observed beneficial effects for facial movement in recognizing famous faces, familiar faces, and unfamiliar faces (Pike et al, 1997 ; Lander et al, 1999 , 2004 ; Lander and Bruce, 2000 , 2003 , 2004 ; Bruce et al, 2001 ; Thornton and Kourtzi, 2002 ; Pilz et al, 2006 ; Roark et al, 2006 ; Lander and Davies, 2007 ; O'Toole et al, 2011 ; Arnold and Siéroff, 2012 ). Based on this body of work, researchers have proposed two mechanisms regarding facial motion's enhancement of recognition: one suggesting that facial movement provides idiosyncratic facial information in addition to static facial information (the supplementary information hypothesis), and the other suggesting that facial movements assist in producing a more robust and flexible three-dimensional face representation in learning new faces, thus improving face recognition (the representation enhancement hypothesis: O'Toole et al, 2002 ; O'Toole and Roark, 2010 ). In the following sections, we will discuss these two hypotheses and their supporting evidence.…”
Section: Facial Motion Improves Face Recognitionmentioning
confidence: 99%
See 3 more Smart Citations